Paths to Success for 7-Eleven in Thailand - Ngaochay, Thanee (Information Management and Business Review, 2011)
This paper reports on an empirical study aimed at elucidating reasons for success in the implementation of strategic decisions by 7–Eleven in Thailand. The 7–Eleven convenience store is a business format franchising operation, which includes the product or service, the brand name or trademark, and the operating system developed by the franchisor and it has experienced significant growth. The Charoen Pokphand (CP) All Public Company Limited (PCL) is the operator of the 7-Eleven convenience stores in Thailand and it has been involved, therefore, with creating opportunities in the franchise system for that market. Potential franchisors have staff trained and support provided for all aspects of their businesses. To have better chances for success, 7-Eleven needs to evaluate itself in order to improve its systems. People are one key success factor in the franchise business, particularly in terms of the representative of the franchisor, who as an agent of the company reflects the company’s image. For the company to achieve sustainable growth, emphasis should be placed on organizational and human resource development. Both parties in the business must provide high levels of cooperation to each other. The franchise business is a special relationship in which the parties can mutually share the benefits.